Effect of taking some of dietary supplements according to special forces exercises to develop some physical abilities, speed and accuracy smash shot for badminton young players - Al-Selmi, A. D. H.; Fenjan, F. H.; Al-Rubaye, S. A. J. (Journal of Human Sport & Exercise, 2019)
Set dietary program for some of dietary supplements and training for badminton young players, and identifying effect of taking some of the dietary supplementary for badminton young players. The research population :( badminton young players group (Arminian club). For age group (16-18) years the sample is divided in to two experimental groups within each group (6) players, and two for the exploratory experiment which was within the research sample, they were divided in to two groups, the first group take some of the dietary supplements (multivitamin creating) .the set exercises by the researchers in the main part of the training unit and the second group (amino acids, vitamins) and the set exercises by the researcher. The scientific approach :( the experimental approach to design the two groups of the pre and posttests). The measurement instruments: physical tests for the explosive power and the power characteristic by speed for the two arms and the legs, besides, the smash shot), after applying the pre-tests, and applying the muscular ability, then applying the exercises for two months set by the researcher. The statistical processing :( the mean was used and the standard deviation and torsion for the one sample, and (t ) test for two independent samples).The research results: ( using the exercises and some of the dietary supplements have positive effect on improving some of the physical abilities, speed and accuracy of smash shot skill for badminton young players). The researcher recommends: (depending exercises accompanying with the dietary supplements for badminton young players of age group (16-18) years by the trainers and using dietary supplements with training and contests to retain the player's energy.